Power struggles and playing politics: An application of Bourdieu's cultural intermediation theory to place marketing. (November 2021) - Warren, Giannina; Dilmperi, Athina; Dinnie, Keith
Abstract: Place branding strategies contribute to policy decisions that shape a city. Little research, however, investigates how place marketers influence the decision-making of those higher up in the value chain. Drawing upon Bourdieu's theory of cultural intermediation, we identify where these professionals exhibit influence in a city branding endeavour and what impact they have on policy decisions. We report results of semi-structured interviews with senior place marketers at 13 cities around the world and find that policy decisions are influenced in unofficial, hidden and non-systemic ways, including identifying and working with key stakeholders behind the scenes, playing politics, and applying a promotional lens to policy endeavours. We discuss these findings and their implications on theory and practice. Highlights: Place marketers influence promotional decisions unofficially and non-systemically. They must negotiate their position of legitimacy, persuasion and influence. They work closely, consistently and behind the scenes with key senior stakeholders. They must be vigilant in their construction of legitimacy. Succeeding in influencing upstream could positively impact the city in the long term.